(untitled) (International relations and international law Journal, 2016)
Economic mechanism of attracting resources in agriculture should spo- sobstvovat formation of competitive financial stability for Agricultural Production . To do this , first of all , the necessary enabling environment for investment in fixed capital industry , which are based on advanced production technology, a set of measures for financial support for their implementation.State support for innovation in the country focused on the development of innovative capacity; increasing the share of high-tech products in the gross domestic product ; facilitate the transition eko¬nomiki Republic of Kazakhstan on the path of innovative development based on the implementation and use of high technology. It is accomplished by complying with national interests in the implementation of innovation; equality of subjects of innovative activity -sti in obtaining state support of innovation; complexity and system of measures to ensure a constant interaction of subjects of innovative activity.